Pola Pengembangan Kompetensi Profesionalisme Guru (Studi Kasus SD Negeri 1 Lipat Kajang Aceh Singkil) - Sapta Priatini (UMSU, 2026)
This study aimed to analyze the pattern of teacher professional competency development through planning, implementation, and evaluation at SD Negeri 1 Lipat Kajang, Aceh Singkil. A qualitative case study design was employed to obtain an in-depth understanding of professional development practices. Data were collected through in-depth interviews, observations, and document analysis involving the principal and teachers, then analyzed using data reduction, data display, and conclusion drawing supported by triangulation to ensure trustworthiness. The findings indicate that professional competency development was systematically planned through academic supervision, teacher needs assessment, and participation in education and training programs. The implementation was carried out through Teacher Working Groups, workshops, seminars, and the utilization of information technology to promote continuous professional learning. Evaluation was conducted through supervision, monitoring, reflective practices, and follow-up activities. These findings demonstrate that collaborative leadership between the principal and teachers plays a strategic role in strengthening teachers’ professional competencies while improving instructional quality and overall educational outcomes in primary schools.